Vivencias de las madres ante hospitalización de su recién nacido en el hospital II Santa Rosa-Servicio de Neonatología - Armas Rodríguez, Carmen Rosa (2023)
This research aimed to comprehensively analyze the experiences of mothers regarding the hospitalization of their newborn in hospital Santa Rosa Piura 2020; With a phenomenological qualitative approach, the sample was determined by saturation and made up of ten mothers. In the treatment of the data the thematic analysis that generated 4 categories was used: Anguish and concern, grief; Impotence pain; Faith in your recovery; Support in their religious beliefs, considered by convergence. In-depth data collection was used, considering core ideas, and then studying the units of analysis in the categories. Results: The experiences of the mothers of the newborns of the Hospital Santa Rosa converged towards anguish and worry, grief, helplessness, faith in their recovery and support in their religious beliefs. The experience of the mother in front of the hospitalization of her son or daughter reflects a complex experience and with a large dose of suffering and pain because the mother sees her son exposed to a technology that he does not yet understand. Mothers show their pain through crying, anguish, sadness, fear, fear, despair and guilt, for hospitalizing their children, they understand that their children need specialized attention. But it is faith in God that helps them continue in their daily struggle and make their child heal